EXAMINING THE FIGURE OF JAVANESE WOMEN FROM THE PERSPECTIVE OF SHORT STORIES BY AUTHORS FROM DIFFERENT ERAS AND ACROSS CULTURES - Chanafiah, Yayah (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Many writers have questioned the figure of women with various local perspectives, such as IBW Widiasa Keniten on Balinese women, H.R. Hidayat Suryalaga on Sundanese women, Mochtar Naim and Sastri Bakri on Minang women, and Umar Kayam who presents portraits of Javanese women. The locality of the female figures as characters presented by these writers strongly depicts their regional characteristics. In the short story entitled Mbok Jah, Umar Kayam, with his sociological background, is able to present a complex and realistic portrait of women. On the other hand, reading the short story entitled Mbah Marinah by Riqqah Dhianty also depicts the locality of Javanese women who work as porters at Bring Harjo Market with all their innocence and simplicity. What is interesting is that the depiction of the figure of Javanese women is presented by young/novice writers who come from ethnicities and cultures outside Java (Sumatra), and are also born in the millennial era. The thick Javanese character of Mbah Marinah is reminiscent of the female character Mbok Jah in Umar Kayam's short story. Both short stories depict a Javanese woman who is very weak, simple, but has strong and steadfast principles. Even in the short story of Mbah Marinah, resignation to her fate as a porter in the market is equivalent to the resignation of the character Mbok Jah as a household helper in Umar Kayam's short story. In this case, the existence of short story writers from different eras and ethnic cultures in questioning the figure of Javanese women who are Javanese, turns out to have equal social and cultural values, so it is very interesting to discuss it in more depth.